Diagnostic and treatment intervals are not associated with survival in rhabdomyosarcoma: A Cancer in Young People in Canada study. Issue 1 (29th August 2021) - Oberoi, Sapna; Lambert, Pascal; Gupta, Abha A.; Deyell, Rebecca J.; Sung, Lillian; Cuvelier, Geoffrey D. E.
Abstract: Background: Delay in diagnosis and treatment initiation can be associated with adverse outcomes in children with cancer. Diagnostic interval (DI) is defined as the time between the date of first health care contact for symptoms related to cancer to the date of cancer diagnosis, and treatment interval (TI) is defined as interval between the definitive cancer diagnosis and cancer treatment initiation. We aimed to determine the predictors of DI and TI in children with rhabdomyosarcoma (RMS) and their association with event‐free survival (EFS) and overall survival (OS). Methods: Using the Cancer in Young People in Canada (CYP‐C) national population‐based database, we conducted a retrospective cohort study of children (0–14.99 years) newly diagnosed with RMS between 2001 and 2015 in Canada. Quantile regression was used to assess the predictors of DI and TI, and Cox regression was used to determine if these intervals were associated with EFS and OS. Results: Median DI and TI were 16.5 days (interquartile range [IQR] 6.0–38.0) and 5 days (IQR 0–12), respectively. DI and TI were not significantly associated with age at diagnosis, sex, race, tumor site, stage or histology, treatment region, distance from treatment center, income quintile or diagnosis year (all p > .05). DI and TI were not associated with EFS (DI: hazard ratio [HR] 1.00, 95% CI 0.96–1.05, p = .871; TI: HR 1.03, 95% CI 1.00–1.05, p = .053) or OS (DI: HR 0.99, 95% CI 0.94–1.05, p = .797; TI: HR 1.02, 95% CI 0.99–1.05, p = .155). Conclusions: In the publicly funded Canadian health care system, DI and TI did not affect the survival of children with RMS.